2022
DOI: 10.3390/pr10112170
|View full text |Cite
|
Sign up to set email alerts
|

Possible Processes and Mechanisms of Hexachlorobenzene Decomposition by the Selected Comamonas testosteroni Bacterial Strains

Abstract: Background: The bacterial destructing activity toward pesticides has been the focus of research in the last few decades. Hexachlorobenzene is included in the organochlorine pesticides group that are prohibited for use. However, large hexachlorobenzene amounts are still concentrated in the soil, stressing the relevance of research on hexachlorobenzene-destroying bacteria. Methods: The ability to destroy hexachlorobenzene by Comamonas testosteroni UCM B-400, B-401, B-213 strains was investigated and established.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Although there is no literature confirming the biodegradability of QNs in Leucobacter sp. currently, Actinobacteria, such as Corynebacterium and Leukobacterium, are often the main carriers of sulfonamide resistance (SR) genes (sul1 and intI1) (Lin et al, 2017;Xia et al, 2019).In previous studies, Comamonas testosteroni has been confirmed to be able to degrade organic substances such as hexachlorobenzene (Dimova et al, 2022), phenanthrene, naphthalene (Goyal and Zylstra, 1997), and 4-chlorophenol (Bae et al, 1997;Wang et al, 2020). What's more, it can be found in Figure 3 that carbon sources have little effect on the community composition of the QNs degrading and tolerant bacteria, the difference between groups is mainly controlled by the type of antibiotics.…”
Section: Species Composition Analysismentioning
confidence: 99%
“…Although there is no literature confirming the biodegradability of QNs in Leucobacter sp. currently, Actinobacteria, such as Corynebacterium and Leukobacterium, are often the main carriers of sulfonamide resistance (SR) genes (sul1 and intI1) (Lin et al, 2017;Xia et al, 2019).In previous studies, Comamonas testosteroni has been confirmed to be able to degrade organic substances such as hexachlorobenzene (Dimova et al, 2022), phenanthrene, naphthalene (Goyal and Zylstra, 1997), and 4-chlorophenol (Bae et al, 1997;Wang et al, 2020). What's more, it can be found in Figure 3 that carbon sources have little effect on the community composition of the QNs degrading and tolerant bacteria, the difference between groups is mainly controlled by the type of antibiotics.…”
Section: Species Composition Analysismentioning
confidence: 99%
“…LB medium had been used to isolate microorganisms from soil to investigate their biotechnological potential 56–58 or to understand the toxicity of chemical agents, such as ENMs. 59–62 Future studies, however, need to consider aqueous solutions more environmentally relevant with closer characteristics to the matrix in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our contrasting results compared to other reports highlight the importance of evaluating the dissolution of the specific compounds in the study as they can differ between manufacturers or product lot. 55 LB medium had been used to isolate microorganisms from soil to investigate their biotechnological potential [56][57][58] or to understand the toxicity of chemical agents, such as ENMs. [59][60][61][62] Future studies, however, need to consider aqueous solutions more environmentally relevant with closer characteristics to the matrix in the study.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of Dimova et al's [20] study was to determine the possible ability of Comamonas testosteroni bacterial strains to degrade hexachlorobenzene (included in the organochloride pesticide group that is banned for use). The ability of the C. testosteroni UCM B-400, B-401 and B-213 strains to decompose hexachlorobenzene was investigated for the first time in the literature, and their destructive activity was confirmed biochemically.…”
mentioning
confidence: 99%
“…Moreover, the microbial consortium (no. 3)-a mixture of all six mentioned strains-exhibited strong degradation activity for all the pesticides and consequently appeared to be a potential inoculum candidate [20].…”
mentioning
confidence: 99%